The targeted podocyte - Agnes B. Fogo (The Journal of Clinical Investigation, 2011)
The podocyte plays a key role both in maintenance of the glomerular filtration barrier and in glomerular structural integrity. Podocyte injury and loss contribute to proteinuria and progressive sclerosis. Inhibitors of mammalian target of rapamycin (mTOR) have variably decreased or caused proteinuria and sclerosis in human disease and experimental settings. In this issue of the JCI, two interesting studies of podocyte-specific manipulation of the mTOR system shed light on the complexity of this pathway in the podocyte.